2018
DOI: 10.5114/wiitm.2018.76263
|View full text |Cite
|
Sign up to set email alerts
|

Is the 8-mm robotic port safe? A case of trocar site hernia after robotic cholecystectomy using the da Vinci Xi system.

Abstract: With the increase in the frequency of robotic surgery, complications have also increased, including trocar site hernias, which rarely occur at the 8-mm port site after robotic cholecystectomy using the da Vinci Xi system. A 37-year-old woman was diagnosed with cholecystitis on abdominal sonography. She underwent robotic cholecystectomy using a bikini-line incision. However, after postoperative day 2, she presented to the emergency room with small bowel obstruction secondary to a herniated bowel loop through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The most dangerous complication of incisional hernia is bowel or omental incarceration. Cases of both types of complications, 5 mm- and 8 mm-trocar site hernias (including omental and small bowel incarceration), following RALS have been repeatedly reported [ 76 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most dangerous complication of incisional hernia is bowel or omental incarceration. Cases of both types of complications, 5 mm- and 8 mm-trocar site hernias (including omental and small bowel incarceration), following RALS have been repeatedly reported [ 76 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sinha et al reported a case of acute TSH from the 8-mm trocar site following robotic hysterectomy and they suspected that the drain placement in the same port was one of the contributing factors. 13 They reviewed the literature, identifying 10 case reports of 8-mm TSH: nine of these with acute presentation, of which three following gynaecologic procedures, [14][15][16] five after urological surgery [17][18][19][20][21] and one after cholecystectomy 22 ; one case of 8mm TSH occurred 32 months after a lower anterior resection for rectal cancer. 23 TSH represents an uncommon complication following minimally invasive surgery, whose incidence varies from 0.1% to 2%.…”
Section: Resultsmentioning
confidence: 99%
“…discussed PSH and reported its incidence as 0.13% in a large series of 11,566 patients (multispecialty group), of which 73% were reported from 8-mm ports. [ 1 ] In addition, 11 such case reports of acute PSH from 8-mm port are also reported in the literature,[ 2 3 4 5 6 7 8 9 10 11 12 ] and only three of these cases were after a gynecological robotic surgery (two benign and one oncology). Our case developed acute PSH at the left 8-mm port following robotic hysterectomy (benign).…”
Section: Discussionmentioning
confidence: 99%